2017
DOI: 10.1002/brb3.804
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in safety issues during Fingolimod therapy: Evidence from a real‐life Relapsing Multiple Sclerosis cohort

Abstract: ObjectiveBenefits and risks of new therapies in Multiple Sclerosis (MS) must be balanced carefully and tailored to patients. We aimed to describe our experience with Fingolimod (FTY), correlating demographics, clinical and hematological features of the Relapsing MS (RMS) cohort with the occurring Adverse Events (AEs).Material and MethodsPretreatment screening tests, cardiological observation, and safety follow‐up data were analyzed in 225 RMS patients. Changes in continuous data were analyzed post hoc with Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…Numerous studies confirm the results of the present study, and it has also been proven that by stopping the use of FTY720, the levels of hepatic transaminase are normalized. [ 24–27 ] In a study performed by Gordo et al, [ 28 ] silymarin had a significant effect on ALT enzyme in patients with chronic hepatitis C. Also, in Hajaghamohammadi et al's [ 29 ] study, they demonstrated a significant decrease in liver enzymes (ALT and AST) after silymarin use in nonalcoholic fatty liver disease. In our study, results demonstrated that the silymarin treatment for 6 months had an effective impact in decreasing the level of oxidative stress such as MDA and increase in antioxidant levels like TAC and TTG.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirm the results of the present study, and it has also been proven that by stopping the use of FTY720, the levels of hepatic transaminase are normalized. [ 24–27 ] In a study performed by Gordo et al, [ 28 ] silymarin had a significant effect on ALT enzyme in patients with chronic hepatitis C. Also, in Hajaghamohammadi et al's [ 29 ] study, they demonstrated a significant decrease in liver enzymes (ALT and AST) after silymarin use in nonalcoholic fatty liver disease. In our study, results demonstrated that the silymarin treatment for 6 months had an effective impact in decreasing the level of oxidative stress such as MDA and increase in antioxidant levels like TAC and TTG.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study conducted in Italy found that ALT and AST abnormalities were detected mostly in men, rather than women, receiving fingolimod, and that a sex-specific approach may be useful for the monitoring of liver enzymes. 35 The factors that might explain such sex-related differences in adherence to laboratory monitoring, and the long-term consequences of them, remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ALT and AST levels can change significantly among different populations (15,16). Despite limited studies concerning confounder effects of demographic features on liver enzyme levels after FT, in general, increased ALT levels were observed 15% more frequently in male patients than in females (22,23).…”
Section: Discussionmentioning
confidence: 99%